Partisipasi Anggota Kelompok Tani dalam Meningkatkan Fungsi Kelompok Tani di Desa Simpang Nungki Kecamatan Cerbon Kabupaten Barito Kuala - Norhayani Norhayani; Luki Anjardiani; Masyhudah Rosni (Universitas Lambung Mangkurat, 2014)
The objectives of this research are: (1) to identify the function of farmer group level, (2) to identify participation level of members of farmer group, and (3) to identify relationship between the participation of members of farmer group with the function of farmer group in Simpang Nungki village Cerbon subdistrict, Barito Kuala district. This research was a survey research. Respondents of this research amounted to 30 farmer taken to the sample proportional random sampling techniques. The research was carried out in Simpang Nungki village Cerbon subdistrict, Barito Kuala district since August until December 2013. Population is all members of farmer group in Simpang Nungki village Cerbon subdistrict, Barito Kuala district (428 farmer). The quantitative data had been analyzed by statistical correlation rank Spearman. Based on the data analysis, the conclusion can be drawn as follows:(1) The function of farmer group level in Simpang Nungki village Cerbon subdistrict, Barito Kuala distri ct is categorized as medium level (80, 40), (2) The participation level of members of farmer group in Simpang NungkI village Cerbon subdistrict, Barito Kuala district is categorized as medium level (103, 67), and (3) there are significant relationshi p between the participation members of farmer group with function of farmer group in Simpang Nungki village Cerbon subdistrict, Barito Kuala district at significant level 95%.